What Does Work Signify for Those in Search of Labor? Meaning of Work for the Unemployed Who Attend an Employee Orientation Program - Navarro-Abal, Yolanda; Climent-Rodríguez, José Antonio; López-López, María José; Gómez-Salgado, Juan (Frontiers in Psychology, 2018)
Introduction: Work is one of the most important areas in people's lives. This is highly related to the meaning of work people possess and the social culture that surrounds them. However, unemployment stands out as a major social phenomenon of the 21st century of concern for governments, institutions and professionals, generating the need to reflect, among other issues, on the processes that favour and keep the person in the situation of unemployment, and to think about the real effects of the measures aimed at supporting and guiding the unemployed. The objective of this work is to analyse the existing differences in relation to societal norms, values, and work centrality in unemployed people who attended employment guidance with respect to another group of unemployed people who didn’t received this guidance. Method: A descriptive, analytical, cross-sectional study was conducted. The sample consisted on a total of 227 users of the Employment Guidance Service Centre of the province of Huelva, who were divided into two groups. A first group of 112 users who make use of the Employment Guidance programmes of the Andalusian Public Employment Services, and a second group, or control group, made up of 115 unemployed people who do not make use of these services. The MOW International Research Group questionnaire have been used for the assessment of the participants. Results: In relation to societal norms, people who do not place their trust in employment guidance conceptualise work as a right and not as a duty; in terms of work values, those with lower levels of training value professional status and prestige with higher scores, whereas people with a higher level of training value the satisfactory nature of work. Regarding centrality, high level results are obtained throughout the sample, and it ranks second only to family when assessing relative centrality. Conclusion: It can be seen how some variables will determine a greater or lesser level of motivation towards the search for employment. This work should lead to a reflection on the need to generate employment insertion programmes that are more adapted to the idiosyncratic characteristics of individuals and groups.